1982
DOI: 10.1055/s-2007-971425
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Ginseng Saponins under Mild Acidic Conditions

Abstract: Ginseng saponins, ginsenosides Rg (1), Re and Rb (1), decomposed under mild acidic conditions to yield prosapogenins. The structures of the prosapogenins were investigated by (13)C-NMR spectroscopy and Rg (1)-prosapogenin II was shown to be a mixture of ginsenoside Rh (1), and its C-20 epimer, produced by hydrolysis followed by epimerization at C-20. Rg (1)-prosapogenin III, the other prosapogenin derived from ginsenoside Rg (1); was a C-25,26 hydrated derivative of Rg (1)-prosapogenin II. Re-prosapogenin II w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
123
1
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(132 citation statements)
references
References 6 publications
5
123
1
3
Order By: Relevance
“…In black ginseng, no Rg 1 was detected, and we found 2.21 ± 0.07 mg of Rb 1 , a significantly lower amount than in the other extracts. During the heating process used to process black ginseng, protopanaxadiol-type saponins including Rb 1 , Rg 1 , Rc, and Rd are converted to ginsenoside Rg 3 by hydrolysis of a sugar residue at C-20 or isomerization of a hydroxyl (OH) group at C-20 [17]. Additionally, the chromatogram of black ginseng extract revealed that approximately 10 ginsenosides were detected after 60 min HPLC retention time (Fig.…”
Section: Saponin Content In Ginseng Extractmentioning
confidence: 99%
“…In black ginseng, no Rg 1 was detected, and we found 2.21 ± 0.07 mg of Rb 1 , a significantly lower amount than in the other extracts. During the heating process used to process black ginseng, protopanaxadiol-type saponins including Rb 1 , Rg 1 , Rc, and Rd are converted to ginsenoside Rg 3 by hydrolysis of a sugar residue at C-20 or isomerization of a hydroxyl (OH) group at C-20 [17]. Additionally, the chromatogram of black ginseng extract revealed that approximately 10 ginsenosides were detected after 60 min HPLC retention time (Fig.…”
Section: Saponin Content In Ginseng Extractmentioning
confidence: 99%
“…Many studies have examined the conversion of ginsenosides by enzymes, [19][20][21][22] heat, and chemicals to increase the amount of ginsenosides with less sugar, 23,24) but these approaches have disadvantages due to increased cost or decreased quality and flavor. Other approaches have been adopted involving fermentation with intestinal bacteria such as Bifidobacterium 25) or lactic acid bacteria, 26) but these methods require expensive media and result in low yields and poor productivity.…”
mentioning
confidence: 99%
“…홍삼은 수삼을 장기간 저장할 목적으로 증숙하여 인삼의 전분을 호화시켜 건조한 것으로 이러한 수 치과정을 거치면서 수삼 또는 백삼과는 다른 유효 성분들이 생성된다고 알려져 있다 2) . 그동안 주로 수삼, 백삼, 홍삼상태 로 건강식품으로 사용되어오던 인삼이 새로운 포제방법에 따 라서 효능이 달라지면서 새로운 가공방법이 많이 나타났는데 주로 열처리 3) , 산처리 4) , 효소처리 5) 및 미생물을 이용한 발효 (Fig. 1-A).…”
unclassified